Forms of Irregular Circumstances in the European Constitutional Area (International Journal of Contemporary Security Studies, 2023)
By reviewing and analyzing the solutions contained in the reference constitutions of European countries, the author tries to systematize the forms of irregular circumstances that are regulated at the constitutional level. A grouping was observed in models according to which there are general provisions on irregular circumstances, as well as those that contain provisions that are individually dedicated to the state of emergency, war and natural disaster. The rule that refers to the general frequency of mutual borrowing of solutions in the constitutions of European countries does not deviate significantly even in the area of ​​regulation of irregular situations. The structure and normative systematics of constitutional acts often indicates whether the author of the constitution pays equal attention to different forms of irregular circumstances, as well as whether he treats them together or separately. Constitutions establish the basis for declaring individual forms of irregular circumstances, as well as entities authorized to make decisions on their introduction and abolition. Restrictions on human rights and basic freedoms are an important topic in constitutional regulation that has points of contact with the irregular situation, and the authors of the paper have given special attention to them.
Keywords: Irregular circumstances; State of emergency; war; State of natural disaster; Comparative constitutional law